Maintenance on steel component for highrise building / Syafawati Nur Hasim - Nur Hasim, Syafawati (2007)
Nowadays, a lot of building in this country are built by practicing a steel as the structure/component of the building including a decorative (exposed structure) of the building as a special image of the building itself. This exposed steel structure needs a lot of maintenance works.The good condition and quality of steel is very important especially to the world class building like Kuala Lumpur City Center (KLCC). The little of this research is Maintenance on Steel Component for Highrise Building. This research will be focus only on the high rise building as mention in writer's objective and scope of study. This topic covered the maintenance of two building which is Kuala Lumpur City Center (KLCC) in Kuala Lumpur and Mesiniaga Tower in Selangor. The objective of this research is to identify the types of steel used in high rise building. Itis also to study the types of maintenance work done to steel structure/component in high rise building. The maintenance of steel structure/component only will be focus to the exposed steel structure. It is because the other steel structure like beams and columns are fully encased by concrete and don't need any maintenance works. Another objective is to identify the benefits of practicing maintenance works on steel structure/component building. The last objective is to compare the maintenance work done to steel structure/component in high rise building. This research is done by the interview with the relevant person of the two selected high rise buildings. The research finding also will include the problems occur on that buildings related to the maintenance on exposed steel structure/component building.